PHARMACOPHORE DEVELOPMENT, ATOM BASED 3-D QSAR AND MOLECULAR DOCKING OF AURORA A KINASE INHIBITORS - CHANDRAKANT G. BONDE, (International Journal of Pharma and Bio Sciences, 2014)
Pharmacophore development, 3D-QSAR and docking studies were performed on twenty eight pyrrolotriazine derivatives as Aurora A kinase inhibitors. Five point pharmacophores with one hydrogen bond acceptor (A2), two hydrogen bond donor (D8, D11), one positive ionic (P15) and one aromatic ring (R17) as pharmacophoric features were developed. Amongst them the Pharmacophore hypothesis ADDPR.55 yielded best survival score 4.687 and was considered to be the best pharmacophore hypothesis. Correlation coefficient of experimental versus predicted Kd of training and test sets is 0.933 & 0.942 respectively. The atom based 3D QSAR was developed with good fitness (r2= 0.9197), efficiency (q2= 0.6372), fisher (F=51.5) and Pearson-R (0.9444). Further the hypothesis was validated by studying the interaction between the ligands and the receptor. The features identified in the pharmacophore showed good interaction between the pharmacophoric site points and the receptor residues. The geometry and features of pharmacophore were expected to be useful for the design of Aurora A kinase inhibitor.